Socialization of Local Wisdom-Based Homestay Management in Sustainable and Environmentally Friendly Hospitality Industry : Pengabdian - I Wayan Adi Pratama; Ni Desak Made Santi Diwyarthi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the capacity of local communities in managing homestays based on local wisdom as part of developing a sustainable and environmentally friendly hospitality industry. The program was conducted in Gianyar Regency, Bali, with 30 participants, a region rich in cultural and natural potential yet still facing challenges in managing tourism accommodations professionally and ethically. The socialization emphasized principles of sustainable tourism, cultural preservation, local value integration, and green hospitality practices. The results showed that the community responded positively, expressing enthusiasm to apply the insights gained, particularly in implementing Tri Hita Karana values and local narratives in homestay development. These findings align with theories such as Community-Based Tourism, Cultural Capital, and the Triple Bottom Line, confirming the importance of culture-based, participatory, and sustainable approaches in building a resilient hospitality sector.